Autonomic and cardiorespiratory responses to the active tilt test in individuals with Parkinson disease: cross-sectional study - Valente, Heloisa Balotari; Gervazoni, Natacha de Lima; Laurino, Maria Júlia Lopez; Vanzella, Laís Manata; Stoco-Oliveira, Mileide Cristina; Rodrigues, Mariana Viana; André, Larissa Borba; Ribeiro, Felipe; Carvalho, Augusto Cesinando de; Vanderlei, Luiz Carlos Marques (Arquivos de Neuro-Psiquiatria, 2022)
Background The Parkinson disease (PD) is frequently associated with autonomic dysfunctions. However, data regarding the influence of PD on the autonomic responses to postural changes is limited.Objective To analyze and compare the autonomic responses, evaluated through linear and non-linear methods of heart rate variability, and cardiorespiratory parameters in two groups: Parkinson disease (PDG) and control (CG), at rest and during the active tilt test.Methods A total of 48 participants were analyzed (PDG: n = 25;73.40 ± 7.01 years / CG: n = 23;70.17 ± 8.20 years). The autonomic modulation and cardiorespiratory parameters were evaluated at rest and during the active tilt test. To assess the autonomic modulation the linear indices, at the time (rMSSD, SDNN) and frequency (LF, HF, LF/HF) domains, and the non-linear indices, obtained through the Poincaré plot (SD1, SD2, SD1/SD2), were calculated. The cardiorespiratory parameters evaluated were heart rate (HR), systolic (SBP), and diastolic blood pressure (DBP), peripheral oxygen saturation (SpO2), and respiratory rate.Results At rest, the PDG presented significantly lower values of rMSSD, SDNN, LF, HF, SD1, SD2, and DBP, and higher values of SpO2. During test, in the PD group, modifications were observed in HR, and SBP, besides a reduced parasympathetic response, and an increased global modulation. The qualitative analysis of the Poincaré plot showed that the PDG has a lower dispersion of the RR intervals during rest and the active tilt test.Conclusion Individuals with PD present reduced global variability and parasympathetic modulation at rest, and reduced parasympathetic response and damage in HR regulation when performing the active tilt test, compared with controls.
Keywords: Arterial Pressure; Autonomic Nervous System Diseases; Heart Rate; Parkinson Disease; Respiratory Rate